Limitations of students with disabilities that hinder the learning process of English as a foreing languaje in semester I in the Foreing Languaje Department, School of Arts and Sciences at The University of El Salvador - Azucena, David Guillermo; Paniagua Mendoza, Carlos Ricardo; Velásquez Mendoza, Claudia Liseth; Mendizábal Arévalo, Odir Alexander; Ayala, Edgar Nicolás (San Salvador, El Salvador : Universidad de El Salvador, 2013)
The following research paragraphs that follow present some serious limitations that complicate the learning process of English as a foreign language of students with disabilities. Two specific cases of students with disabilities were selected to execute a study case on each one. Both of them were active students during first semester of 2013 at University of El Salvador. The limitations that become more difficult as the process of learning English as a foreign language for a student with a disability at the University of El Salvador are related to disabilities in History. By demonstrating that they have been excluded from public service access including health, education and jobs opportinities that all citizens must have, people with disabilities have been perceived by authorities and other social groups under a prejudgement that reduces and limits their abilities; this explains partially why they still face serious educational limitations. The most common limitations that handicap students relate to are external and internal limitations. External limitations refer to the lack of physical access and bibliographical resources, ¨especially¨ in Braille, infrastructure which does not offer any type of accessibility for the disabled and curriculum adaptations. The internal limitations include a pedagogical practice that ignores any methodological effort to integrate and adapt to the circumstances of students with disabilities as well as the perception from the teacher and other students represent serious limitations in the learning process of English a foreign language.
Incluye anexos.
Tesis para optar al título de -- (Licenciatura en Lenguas Modernas especialidad Francés e Inglés) -- Universidad de El Salvador, San Salvador, 2013
Bibliográfia : hojas 34-36
Keywords: Inglés -- Enseñanza; discapacitados